2017
DOI: 10.1001/jamasurg.2017.1088
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences of Trauma Resuscitation

Abstract: Although the urgency of trauma care limits explicit discussion and consideration of patient priorities, we found that patient concerns corresponded well with trauma team goals. Patients perceived trauma team members as competent, efficient, and caring. Focusing on patient communication could further improve patient-centeredness in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…They trusted the organisation and experienced it to be mostly well-organised and efficient, mainly because of what they considered to be a wellfunctioning system, but also due to caring actions from doctors and nurses. This has been confirmed by other studies in similar settings 31,54,57,58,[80][81][82] and is re-assuring. What is alarming is that patients experienced fear, pain, lack of information and some patients felt excluded from what was going on.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…They trusted the organisation and experienced it to be mostly well-organised and efficient, mainly because of what they considered to be a wellfunctioning system, but also due to caring actions from doctors and nurses. This has been confirmed by other studies in similar settings 31,54,57,58,[80][81][82] and is re-assuring. What is alarming is that patients experienced fear, pain, lack of information and some patients felt excluded from what was going on.…”
Section: Resultssupporting
confidence: 86%
“…The patients wanted to be involved in their care pathway. 31,54,57 We find it of outmost importance to communicate the findings to doctors and nurses who treat trauma patients, in order to strengthen patient-centred care and include the patients in their care to a greater extent than what is shown in study II. To keep focus on the patient during the whole period in the trauma room is important to improve patient satisfaction and avoid uncertainties among patients.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Patients' experiences mainly included emotional responses of being generally happy about still being alive despite the trauma and residual deficits. Kaufman et al 14 examined different aspects of trauma patients' experiences during the acute phase and found that their experiences were dependent largely on trauma team members' demeanour, expertise, and efficiency and they valued clear clinical communication. These positive experiences may largely be influenced by the initial, longer term and holistic management provided by the MTC.…”
Section: Discussionmentioning
confidence: 99%